The HIV Risk Profiles of Latino Sexual Minorities and Transgender Persons Who Use Websites or Apps Designed for Social and Sexual Networking - Sun, Christina J. (Health Educ Behav, 2015)
The use of websites and GPS-based mobile applications (“apps”) designed for social and sexual networking has been associated with increased HIV risk; however, little is known about Latino sexual minorities’ and transgender persons’ use of these websites and apps and the risk profiles of those who use them compared with those who do not. Data from 167 participants who completed the baseline survey of a community-level HIV prevention intervention, which harnesses the social networks of Latino sexual minorities and transgender persons, were analyzed. One quarter of participants (28.74%, n = 48) reported using websites or apps designed for social and sexual networking, and 119 (71.26%) reported not using websites or apps designed for social and sexual networking. Those who used websites or apps were younger and reported more male sex partners, a sexually transmitted disease diagnosis, and illicit drug use other than marijuana. HIV prevention interventions for those who use websites or apps should consider addressing these risks for HIV.